Towards digital counselling in primary care management of symptomatic knee osteoarthritis: a qualitative descriptive study in Finnish primary care - Miia Jansson; Maria Kääriäinen; Gillian Vesty; Minna Pikkarainen (Finnish Social and Health Informatics Association, 2023)
Digital counselling may improve patients' health outcomes, when eHealth solutions are accessible and tailored to the patients' needs, which is especially important for people with chronic and long-term conditions such as knee osteoarthritis. This study aims to identify patients' eHealth needs to improve the quality of digital counselling in a primary care management of symptomatic knee osteoarthritis. A qualitative study was used to collect patients' eHealth needs through semi-structured interviews in a single outpatient clinic in Finland between August 2020 and November 2020. The data was analyzed using both deductive and inductive content analysis approaches. The study was reported in accordance with the Consolidated Criteria for Reporting Qualitative research checklist to improve the transparency of the study. Analysis of the data revealed five main categories to be considered when implementing digital counselling in patients with symptomatic knee osteoarthritis: background factors (functional impairments, health literacy, digital literacy, cost-related access barriers), resources (digital methods and materials), sufficiency (knee osteoarthritis-related knowledge and skills), implementation (simplicity, trust, patient-centeredness), and benefits (self-care capabilities, confidence). According to our findings, both health and digital literacy seems to be important contributors to the adoption of digital counselling in a primary care management of symptomatic knee osteoarthritis. New eHealth solutions should not replace the first visit in the outpatient clinic. Instead, the use of eHealth solutions should be based on the first visit, during which a trusting relationship between patients and healthcare providers is established. In future, the level of health and digital literacy in patients with symptomatic knee osteoarthritis should be taken account.